A LONG-TERM ECONOMIC MODEL: CASE OF ALBANIA - Ceko, Enriko (European Scientific Journal, ESJ, 2013)
Purpose of the research is to give an economic model for Albania based on its human and natural resources, a model which guarantees economic growth, sustainable development and a path towards integration of the country in the Balkan region and beyond. Approach used is based on relations between sectors of the Albanian economy and relations of Albanian economy with those of countries around and the European economy, aiming providing of products and services for local consumption and exports, for a better balance between exports and imports, as a tool for GDP icrease. Seven economic models have been identified until now. The model which fits the best under Albanian conditions is the one tha support economic development defining sectors where human, natural and financial resources should be focused. To build such a model between sectors the most suitable activities to be followed should be selected. This could be done with methods that take under the consideration three variables: production, savings and labour. According to the conditions of our country and available resources, economic development have more chances to flow in the road of trade economy towards sustainable development. Inside this system, Albanian economy has the chances to be a succesful one in the road of perfectioning anglosaxon model, inside this model, the most suitable segment for the surrent conditions and for the future is: exploitation/production from soil/underground of raw materials – agricultural and rural development – agribusiness – finnished goods manufacturing – proccesing goods for consumption – construction/building materials – textile industry aiming foreign markets/qualitative luxury products – energy capacity increase – wholesale and relate sectors development – widening transport capacities – development of relaxe businesses – tourism development – development of insurance and banking sector – IT investments – health services improvement – development of consultancy sector – strength of education system. The major result and implications is that following that economic model increases chances for improving life quality of Albanians and helping local economy to gain competitive advantages, towards the path of European integration